Chronology and periodicity of linear enamel hypoplasia mmong Late/Final Jomon period foragers: Evidence from incremental microstructures of enamel. (16th June 2016) - Temple, Daniel H.
Abstract: This study estimates age-at-defect formation and periodicity of linear enamel hypoplasia (LEH) using incremental microstructures of enamel. Results are compared to previous studies and between sites from different regions of Japan (Costal Honshu, Inland Honshu, and Hokkaido). High resolution impressions were collected from the dental remains of 32 individuals from nine archaeological sites. Casts were produced from these impressions and studied under an engineer's measuring microscope. LEH were identified based on enamel surface depressions and accentuated perikymata. Age-at-defect formation was estimated using histological methods. LEH periodicity was estimated using counts of perikymata between defects. Age-at-defect formation ranged between 1.1 and 5.8 years, while interquartile ranges were between 2.9 and 4.1 years. LEH periodicity ranged between 0.1 and 1.7 years, with an average of 0.2 years. There were no significant differences in average age-at-defect formation between regions. Significantly higher LEH periodicities were observed among Jomon foragers from Hokkaido and Inland Honshu compared to Coastal Honshu. Earlier ages-at-defect formation and lower stress periodicities were found by this study compared to earlier research. These differences are attributed to the inclusion of individuals with intact tooth crowns and use of objective, microscopic methods to identify LEH. The interquartile ranges for ages-at-defect formation are consistent with isotopically estimated ages for reductions in breast milk consumption. The lack of differences in average age-at-defect formation between geographic groups may reflect similar environmental stress burdens associated with this process. Comparatively shorter intervals between defects among Late/Final Jomon foragers from Coastal Honshu suggest elevated ecological stress burdens among this sample.